PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2002-2011 - YUSTINA SARI, MELINDA Yustina (Jurnal Akuntansi AKUNESA, 2013)
The main objective of this research was to determine the effect of Good CorporateGovernance to the financial performance of the company. Total observation are200 they are 20 companies that listed on Bursa Efek Indonesia by 2002 to 2011.They were chosen by purposive sampling method. Analysis model of the data usedin this research was a simple linear regression model. Corporate Governance asmeasured by CGPI based on the rating that has been prepared by IICG and thefinancial performance is measured by Return On Equity. The results of thisresearch show that GCG has no effect on the financial performance partially.ROE can not be explained by the GCG.Keywords: Good Corporate Governance, Return on Equity